2020
DOI: 10.1186/s12985-020-01451-6
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits respiratory syncytial virus replication by regulating the MiR-155/SOCS1/STAT1 signaling pathway

Abstract: Background Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infection in infants, children, immunocompromised adults, and elderly individuals. Currently, there are few therapeutic options available to prevent RSV infection. The present study aimed to investigate the effects of luteolin on RSV replication and the related mechanisms. Material and methods We pretreated cells and mice with luteolin before infection with RSV, the virus titer, expressions of RSV-F, interferon (IFN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…The evidence of TRIM22 antiviral activity against RSV is founded on in vitro infection of permissive cells in which TRIM22 expression was downregulated by RNA interference. An increase in viral RNA expression was detected in TRIM22 knocked-down cells, as compared to control cells [108]. However, the mechanism of RSV restriction by TRIM22 remains to be elucidated.…”
Section: Other Rna and Dna Virusesmentioning
confidence: 94%
See 1 more Smart Citation
“…The evidence of TRIM22 antiviral activity against RSV is founded on in vitro infection of permissive cells in which TRIM22 expression was downregulated by RNA interference. An increase in viral RNA expression was detected in TRIM22 knocked-down cells, as compared to control cells [108]. However, the mechanism of RSV restriction by TRIM22 remains to be elucidated.…”
Section: Other Rna and Dna Virusesmentioning
confidence: 94%
“…Very recently, a report has shown that TRIM22 exerts an inhibitory activity on respiratory syncytial virus (RSV) [108]. RSV is a negative single-stranded RNA virus that belongs to the family of paramyxoviridae.…”
Section: Other Rna and Dna Virusesmentioning
confidence: 99%
“…In terms of chemical properties, most ingredients were identified as flavonoids, natural polyphenols with presumed beneficial effects on anti-inflammation, antioxidation, and immunomodulation ( Yi, 2018 ; Zeng et al, 2019 ). Previous findings confirmed that the main flavone constituents in QF, such as Quercetin and Luteolin, could inhibit RSV replication by directly blocking viral adhesion or modulating microRNA-related signaling pathways ( Wang S. et al, 2020 ; Lopes et al, 2020 ). Although there was no literature reporting direct links between RSV and Kaempferol, Naringenin, or Isorhamnetin, these compounds are reported to play critical roles in antiviral and anti-inflammatory procedures by reducing viral replication, inhibiting inflammatory cytokines, and eliminating free radicals in respiratory tract viral diseases ( Yang et al, 2019 ; Huang YF.…”
Section: Discussionmentioning
confidence: 57%
“…Wang et al reported that luteolin, a common bioflavonoid found in fruits and vegetables, increased the production of ISGs by enhancing STAT1 phosphorylation, resulting in an inhibition of RSV replication. 38 Kawaguchi et al reported that the bioactive constituent tryptanthrin, found in the indigo plants Polygonum tinctrorium and Isatis tinctoria, altered STAT1 phosphorylation and nuclear translocation in HU-VECs. 39 In the present study, we found that compared to that of the untreated group, the expression levels of If it1, If it2, Isg15, and Ccl5 mRNA in the 5-HMF-treated macrophages infected with VSV were significantly upregulated (Figure 3).…”
Section: ■ Discussionmentioning
confidence: 99%